Utilization of immunization service and predictors among under 3-year-old children in urban slums of Chanmyathazi Township, Mandalay, Myanmar - Win Lae Lae (2019)
© 2018, Medical Association of Thailand. All rights reserved. Objective: To identify the prevalence of immunization and predictors of utilization of immunization service among under-3-year-old children in urban slums of Chanmyathazi Township, Mandalay. The outcome variables used for the present study were whether the child received complete types of EPI immunization, immunization with timeliness and utilization of immunization service. Materials and Methods: A cross-sectional community surveys by using cluster sampling was applied to select 429 primary caregivers of under-3-year-old children. Face to face interview was conducted using four parts of structured questionnaire. Chi-square test and multiple logistic regression were performed to examine factors associated with utilization of immunization. Results: The prevalence of the children with complete and partial type of immunization according to national schedule were 24.1% and 64.8%, respectively, whereas 11.1% of them were never immunized. Regarding timeliness, 26.5% of the immunized children had the timely vaccinations, while about three-quarters (73.5%) had delayed immunization. In terms of utilization of immunization status, 23% of the caregiver utilized the service with quality immunization and 77% of them did not utilize the service. In multiple logistic regression analysis, child age (AOR 3.49, 95% CI 1.63 to 7.50), income (AOR 6.36, 95% CI 2.35 to 17.18), migration status (AOR 3.28, 95% CI 1.05 to 10.29), ANC visit (AOR 4.77, 95% CI 1.55 to 14.67), receiving additional vaccine (AOR 6.27, 95% CI 2.72 to 14.44), and having immunization card (AOR 3.15, 95% CI 1.33 to 7.46) were significantly predicted for the utilization of the immunization service (p-value <0.05). Conclusion: This study found that a comprehensive maternal and child health care system that promote ANC together with immunization uptake and health promotion programs on additional vaccine for preventable diseases such as Rotavirus infection and Japanese encephalitis in the community level is needed. Using appropriate software to keep health records in form of electronic registration for slum migrants is also needed.